Potassium channel β-subunits as voltage-controlled biochemical memories - Rorsman, HO (2022)
Recent work has demonstrated a role for Reactive Oxygen Species (ROS) in promoting sleep. In the Drosophila melanogaster brain, two dozen sleep-inducing neurons with projections to the dorsal fan-shaped body (dFB) integrate cumulative ROS burden over the duration of the day. The neurons’ exposure to ROS is thought to be integrated by the Kv channel Shaker’s β-subunit Hyperkinetic, whose oxidoreductase domain metabolises ROS-derived aldehydes with the help of a nicotinamide adenine dinucleotide phosphate (NADPH) co-factor. ROS exposure oxidises this co-factor to NADP+ and slows the inactivation of the Shaker-mediated A-type current, which is permissive of higher frequency neuronal activity and thereby aids sleep promotion. Typical models of homeostatic sleep posit that gradual integration of sleep promoting signals (e.g. ROS) must rapidly dissipate following sleep induction. However, the specific identity of ROS signalling molecules and how these signals are dissipated remains unclear.